The impact of time‐varying clinical surrogates on disparities in African‐American kidney transplant recipients – a retrospective longitudinal cohort study. (16th September 2018) - Taber, David J.; Su, Zemin; Fleming, James N.; Pilch, Nicole A.; Morinelli, Thomas; Mauldin, Patrick; Dubay, Derek
Summary: An improved understanding of the impact of clinical surrogates on disparities in African‐American (AA) kidney transplantation (KTX) is needed. We conducted a 10‐year retrospective longitudinal cohort study of electronically abstracted clinical data assessing the impact of surrogates on disparities in KTX. Clinical surrogates were assessed by posttransplant year (1, 2, 3 or 4) and defined as acute rejection (Banff ≥1A), mean SBP >140 mmHg, tacrolimus variability (CV) >40%, mean glucose >160 mg/dl and mean hemoglobin <10 g/dl. We utilized landmark methodology to minimize immortal time bias and logistic and survival regression to assess outcomes; 1610 KTX were assessed (54.2% AAs), with 1000, 468, 368 and 303 included in the year 1, 2, 3 and 4 complete case analyses, respectively. AAs had significantly higher odds of developing a clinical surrogate, which increased in posttransplant years three and four [OR year 1 1.99 (1.38–2.88), year 2 1.77 (1.20–2.62), year 3 2.35 (1.49–3.71), year 4 2.85 (1.72–4.70)]. Adjusting for the five clinical surrogates in survival models explained a significant portion of the higher risks of graft loss in AAs in post‐transplant years three and four. Results suggest focusing efforts on improving late clinical surrogate management within AAs may help mitigate racial disparities in KTX.